تطوير المادة التعليمية لمهارة الكلام علي أساس النظرية المعرفية بجامعة بنجكولو الاسلامية الحكومية - dibi afriansyah (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
AbstrakAt the Institute of Islamic religion of Bengkulu There is an Arabic Language Education faculty. In this faculty students are taught Arabic skills, be it listening skills, speaking skills, reading skills and writing skills. The material used to teach speech skills is teaching material written and composed by "Yeni fatriani" consisting of material of dialogue and grammar material, and this material in the form of printed book format, and the method used is direct method. So researchers see that the problem in teaching the speaking skills in this faculty is the teaching materials used, the teaching materials used are not in the form of a special book of speaking learning, and have not been prepared in accordance with the cognitive process. As it is known that the learning process is a cognitive process, so that researchers develop teaching materials speaking skills based on cognitive theory, And researchers see that this theory in accordance with the stages of the process of speaking, because the process of language lies in the brain.Based on the introduction above, the researcher presents the following research problem formulation: (1) How to develop teaching material of speech skill based on cognitive theory at institute of Islamic religion of Bengkulu. (2) What are the characteristics of speaking skills teaching materials developed based on cognitive theory in institute of Islamic religion of Bengkulu. (3) How is the effectiveness of teaching skill material developed based on cognitive theory at institute of Islamic religion Bengkulu. The purpose of this research are: 1) Creating teaching materials product speaking skill based on cognitive theory for students of institute of Islamic religion of Bengkulu 2) Knowing the characteristics of teaching materials for speaking skills on the basis of cognitive theory, 3) Knowing the effectiveness of the application of teaching materials that have been developed in improving the ability to speak the students of institute of Islamic religion of Bengkulu.This research was conducted by using qualitative and quantitative approaches to Borg and Galll's experimental and development methods (Research & Development) written by Sugiyono. This research produces a product. The results of this study are: (1) teaching material of speaking skill based on cognitive theory for student of institute of Islamic religion of Bengkulu. with the following development procedures: needs and problem analysis, data gathering, Product design, product validation, product improvement, product validity test, field test, and final improvements. (2) Characteristics of educational materials consist of cognitive processes, namely: attention, interpretation, arrangement of grammar and store it in memory, and repetition. (3) The results of this study indicate that the use of teaching materials developed is very effective in helping students improve their speaking and expression skills with Arabic. The effectiveness of the product can be seen from the results of pre test and post test of students tested through t test, then the value obtained from pre-test 2010 and post test 2345, with a success rate of t test 27.75% of the df level (32) is 1.711 and the score derived from mathematical calculations is 71, 06. This statistical calculation shows that the value of the independent test t is 4825 greater than the value (t table) 1.711 (1.711 <27.06). and supported by questionnaires of lecturers and students, each scored 82% and 84%, then with these values it can be concluded that the developed material is acceptable.